Ascorbic acid and selected preservatives influence effectiveness of UV treatment of apple juice - Usaga Barrientos, Jessie (2017)
The influence of ascorbic acid, sodium benzoate, potassium sorbate, and sulfur dioxide on the effectiveness of UV pasteurization of apple juice and the effect of UV exposure on the stability of these compounds were evaluated. The concentration of ascorbic acid, total vitamin C, benzoate, sorbate, and sulfur dioxide, and the juices' physicochemical properties were determined. UV treatment consisted of multiple passes at a fixed dose of 14 mJ cm−2 per pass, achieved by adjusting the juice flow rate through the UV machine. Samples containing ascorbic acid were inoculated with Escherichia coli ATCC 25922 (107 CFU ml−1) and analyzed for microbial reduction due to UV. The addition of ascorbic acid, sorbate, and benzoate significantly increased juices' absorption coefficients, which caused a reduction in the juice flow rate (p < 0.05) required to achieve the fixed UV dose. UV treatment had no significant effect on total vitamin C and benzoate concentrations (p > 0.05) but decreased sulfur dioxide, ascorbic acid, and particularly sorbate levels (p < 0.05). Increases in ascorbic acid concentration decreased inactivation of E. coli (p < 0.0001). Thus, additives than can either adversely influence UV efficiency or be degraded due to UV exposure should be added after UV treatment.